The Short Dramatic Form in the Works of Kostas Ostrauskas and Juozas Erlickas - Klišienė, Neringa (Literatūra, 2023)
Short dramatic forms have become theatrical objects that are not easily identifiable. They act as a symbol of questioning the foundations of the conventional drama and a reflection on the dramatic genre in general. The article focuses on its ambiguous treatment and its actualisation in the context of contemporary Lithuanian dramaturgy. Micro-drama, miniature, one-shot drama, or ‘dramatized’ proverbs and sayings – these are the playwrights’ own denominations indicating a kind of tendency which emerged at the end of the 20th century, or, at least, the search for an original term or word. At the same time, however, this effort also signals the inscription of short-format dramatic texts into a certain mediatic area of literature and theatre, which is primarily seen as a sign of a certain bargain with the reader. The article does not look at short-form texts so much through the prism of theatrical evolution, but rather focuses on the mechanism of short-form writing. The question is whether (and how) such ‘mutations’ of dramatic writing maintain a specific theatrical mode of operation (the plot, the character etc.) when they enter the dynamic field of the short form. It is concluded that its mechanism is related to maximum cost-effectiveness and economy of language, and, through the reduction of the aforementioned dramatic triad, the function of the perceiver and his/her interpretative work are radicalised.